Local Wisdom Values in the Tradition of Tedhak Siten in the Era of Globalization - Faisol Hakim; Bahrudin, Babul; Suwandi, Mohamad Ardin (Amorti: Jurnal Studi Islam Interdisipliner, 2023)
Era of globalization. The cultural and religious values ​​contained in this tradition make it an integral part of local community life. Despite living in modern times with the significant influence of globalization, the Tedhak Siten In the current era of globalization, local traditions often face various challenges. Globalization brings foreign cultural influences that can change the way of life and values ​​of local communities. The influence of technology, social media, influences the way local people view and practice their traditions. This research aims to analyze the role of the Gununggeni village community regarding the Tedhak Siten tradition as local wisdom in the era of globalization. This research uses qualitative methods, with a case study type of research. Data collection techniques were carried out through in-depth interviews, observation and documentation. The validity of the data uses source triangulation and theory triangulation. Data analysis techniques use data collection, data reduction, data presentation, and data verification or conclusions. The research informants consisted of several people from Gununggeni village and several young people from Gununggeni village. The results of this research are that the Tedhak Siten tradition in Gununggeni Village has a strong existence even though it is in the tradition is still preserved and considered an obligation by the village community.